THE MOST IMPORTANT ASPECTS OF STUDYING TERM VOCABULARY WITH STUDENTS OF ENGINEERING AND TECHNICAL SPECIALTIES - Zoriana Y. Kunch (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The paper outlines the most relevant aspects of the study of term vocabulary while working with students of engineering and technical specialties. A number of general scientific research methods were used: analysis, classification, systematization, interpretation. This made it possible to solve a number of specific tasks: a) to identify the most relevant issues in the current context of terminology and group them into certain areas of study; b) describe typical problems related to the understanding of each aspect; c) identify the latest challenges in the study of term vocabulary and propose original approaches to their analysis. Emphasis is placed on five problematic issues that are especially important in the current context of globalization of society and internationalization of the educational process. Firstly, clarification of the basic concepts of terminology (term, terminology, terminological system) and the specifics of the term as a special language unit, characterized by standardized, unambiguous, systematic, and so on. Secondly, determining the ratio of national and borrowed in terminology. This problem is still acute, as at the present stage Ukrainian terminological systems are under intense foreign influence, including the saturation of English-language elements. Thirdly, the study of the experience of terminological work in the historical and comparative context, which allows modern scholars to involve in the terminological systems of previous periods and the most suitable examples of terminological creation of other languages. Fourthly, the study of the functional characteristics of term vocabulary, in particular the processes of terminologisation and determinologisation, because in the context of intellectualization of modern society is intensive migration of vocabulary from industry terminologies to general literary language and vice versa. Fifthly, the analysis of cultural problems of scientific and technical speech, as in the terminology and in general in the scientific style of the literary Ukrainian language there are numerous deviations from the norm, partly related to phonetic and orthographic adaptation of borrowed terminological units. It is highlighted that all these aspects are inextricably linked, and the study of term vocabulary requires a comprehensive approach and systematic work with students. Linguistic competence of future scientists and engineers involves a high culture of speech, highly skilled vocabulary due to the need for accurate and normative professional communication at all levels of professional activity, the ability to responsibly and on the basis of thorough mastery of all aspects of terminology analysis implement them in all areas of scientific and technical development to ensure the harmonious and full development of Ukrainian scientific and technical terminology. Prospects for further research are identified in the detail of these five main aspects in the context of individual terminological systems.